Antifungal activity of the ribosome-inactivating protein BE27 from sugar beet (Beta vulgaris L.) against the green mould Penicillium digitatum - Citores, Lucía (2016)
The ribosome-inactivating protein BE27 from sugar beet (Betavulgaris L.) leaves is an apoplastic protein induced by signallingcompounds, such as hydrogen peroxide and salicylic acid, whichhas been reported to be involved in defence against viruses. Here,we report that, at a concentration much lower than that present inthe apoplast, BE27 displays antifungal activity against the greenmould Penicillium digitatum, a necrotrophic fungus that colonizeswounds and grows in the inter- and intracellular spaces of thetissues of several edible plants. BE27 is able to enter into thecytosol and kill fungal cells, thus arresting the growth of thefungus. The mechanism of action seems to involve ribosomal RNA(rRNA) N-glycosylase activity on the sarcin?ricin loop of the majorrRNA which inactivates irreversibly the fungal ribosomes, thusinhibiting protein synthesis. We compared the C-terminus of theBE27 structure with antifungal plant defensins and hypothesizethat a structural motif composed of an α-helix and a β-hairpin,similar to the γ-core motif of defensins, might contribute to thespecific interaction with the fungal plasma membranes, allowingthe protein to enter into the cell.